It is not power, but how you use it: Experimental evidence on altruism from households in Pakistan. Issue 5 (11th March 2020) - Said, Farah; Mahmud, Mahreen; D'Adda, Giovanna; Chaudhry, Azam
ABSTRACT: We investigate altruism among household members in the presence of information asymmetry using artefactual experiments in Pakistan. Having a family member who does not respect one's control over earned property makes generosity less likely within the experiment. Women, who display greater entitlement over own earnings, are less generous when they can conceal their allocation decisions, showing that self-regarding behaviors are driven by pent-up demand for household members to respect their control over resources. Our findings reveal that understanding household dynamics can be critical for policy makers wanting to maximize welfare outcomes in social protection programs.